Exploring the Effects of Collaborative Writing on Students’ Argumentative Essays and Their Perceptions about Its Implementation - Faradila Masuara; Utami Widiati (English Language Teaching and Research, 2020)
This study aims at exploring the effects of collaborative writing (CW) on students’ argumentative essays and their perceptions about its implementation. It involved 42 students from a state university in Indonesia, grouped into two: 14 students of control group and 28 of experimental group. In the control group, argumentative writing tasks were completed individually; in the experimental group, these tasks were conducted in pairs. Writing quality was determined by a holistic rating procedure that included content, organization, grammar, vocabulary, and mechanics. Results of the study showed that CW had an overall significant effect on students’ L2 argumentative writing quality.  However, this effect varied from one writing aspect to another; the effects were significant for content, organization, and vocabulary, but not for grammar and mechanics. In addition, the findings also revealed that the students enjoyed the CW activitis, and most of them perceived CW positively as it improved their L2 writing performance. Keywords: argumentative writing, collaborative writing, writing quality, students’ perception